2010
DOI: 10.1016/j.bbadis.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of F508del CFTR in native human colon

Abstract: The major cystic fibrosis mutation F508del has been classified by experiments in animal and cell culture models as a temperature-sensitive mutant defective in protein folding, processing and trafficking, but literature data on F508del CFTR maturation and function in human tissue are inconsistent. In the present study the molecular pathology of F508del CFTR was characterized in freshly excised rectal mucosa by bioelectric measurement of the basic defect and CFTR protein analysis by metabolic labelling or immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 41 publications
(87 reference statements)
3
36
1
Order By: Relevance
“…Hence, there is an evident genotype-phenotype correlation between CFTR expression and MI. Prior studies suggest that intestinal F508del CFTR can be partially processed to form band C in humans and pigs (33,35,36). Whether GCC signaling in the gut renders the potential of intestinal epithelial cells in these species to process mutant CFTR protein warrants accumulating more experimental evidences.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is an evident genotype-phenotype correlation between CFTR expression and MI. Prior studies suggest that intestinal F508del CFTR can be partially processed to form band C in humans and pigs (33,35,36). Whether GCC signaling in the gut renders the potential of intestinal epithelial cells in these species to process mutant CFTR protein warrants accumulating more experimental evidences.…”
Section: Discussionmentioning
confidence: 99%
“…As noted previously, the F508del CFTR mutation differs from G551D in that it primarily interrupts trafficking of CFTR to the plasma membrane. However, some studies suggested that small amounts of F508del CFTR may be at the plasma membrane of some patients with F508del CF and thus are available for potentiation by ivacaftor [Van Barneveld et al 2010]. Adults with CF were enrolled in a 16-week double-blind trial with 4:1 randomization to ivacaftor versus placebo (part A).…”
Section: Clinical Trials Of Ivacaftor Monotherapymentioning
confidence: 99%
“…Non-CF lung epithelium specimens were analyzed from parts of non-CF donor lung explants that showed regular histology of airway epithelium and submucosal glands. Rectal biopsies were collected with a suction biopsy device from F508del homozygous CF subjects and non-CF healthy volunteers [14]. T84 cells were cultured in DMEM/Ham-F12 medium supplemented with 5% (v/v) fetal calf serum at 37°C in a 5% CO 2 atmosphere.…”
Section: Tissues and Cell Linesmentioning
confidence: 99%
“…Only few studies examined mutant CFTR in human tissue, i.e. sweat gland [11,12], intestine [12][13][14], nasal polyps [12] and lungs [15]. In the context of the upcoming studies on correctors and potentiators of mutant CFTR [16,17] it is important to enlarge our knowledge about mutant CFTR protein biochemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation